1972
DOI: 10.2466/pms.1972.34.2.663
|View full text |Cite
|
Sign up to set email alerts
|

Sex Influence in Aesthetic Behavior

Abstract: Two studies of the influence of sex on aesthetic behaviour of art purchasers show significant effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
2
14
0
1
Order By: Relevance
“…• Three different measurements of complexity: Gif ratio, Edge length and the average cell size (average blob size, ABS). • Results support Soueif & Eysenck's (1971: 1972 findings regarding preferences for reflectional and rotational symmetry, and a greater preference for simplicity in Egyptian participants.…”
Section: Highlightssupporting
confidence: 82%
See 1 more Smart Citation
“…• Three different measurements of complexity: Gif ratio, Edge length and the average cell size (average blob size, ABS). • Results support Soueif & Eysenck's (1971: 1972 findings regarding preferences for reflectional and rotational symmetry, and a greater preference for simplicity in Egyptian participants.…”
Section: Highlightssupporting
confidence: 82%
“…It is possible that there are sex differences in preference for specific symmetries in relation to human judgments of visual art and abstract patterns (see Bernard, 1972;Humphrey, 1997;Johnson & Knapp, 1963). It is also possible that male and female aesthetic judgments for symmetry are based on a difference in perceived complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature reports gender difference in the appreciation of painting styles, but the direction of this difference is not clear and is not consistently reported. Bernard (1972), for example, found that women are more attracted to impressionist paintings than men, and men are more attracted to "modern paintings" than women. Neperud (1982) found that women showed less preference for artistic patterns than men, whereas men rate figurative, i.e., realistic, and abstract styles more favourably than women (see Polzella, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…El estudio que puede considerarse como el más sistemático entre los que buscan los determinantes socioculturales del gusto en materia de pintura, es la investigación llevada a cabo por Bernard (1972), en la que observó y analizó las compras efectuadas por 480 sujetos en una tienda de reproducciones de cuadros, el autor establece una correspondencia entre el contenido de las elecciones y el conjunto de las variables sociales o culturales que pueden caracterizar a cada uno de los sujetos.…”
Section: Perspectiva De Desarrollo Y Aplicación Del Ars En El Diseño unclassified